Topic Modelling Analysis to Explore Policy Considerations Regarding the Practical Introduction of Affirmative Action in the Field of Education - Jang, Ji-Hyun (EAI Endorsed Transactions on Scalable Information Systems, 2023)
The aim of this study is to explore the policy considerations that should be taken into account regarding the practical introduction of affirmative action policies in the field of education. For this purpose, we analysed the 100 most relevant YouTube videos produced between 2015 and 2023 using network analysis, the aim being to utilize the material they provide on affirmative action so as to reflect this in future education policies. As a result, nine key policy considerations that should be considered when introducing affirmative action policies in the field of education were derived.
Keywords: affirmative action in the field of education; big data analysis; YouTube video analysis